Amplification of anticancer efficacy by co-delivery of doxorubicin and lonidamine with extracellular vesicles - Huizhen Li; Wan Xu; Fang Li; Ru Zeng; Xiuming Zhang; Xianwu Wang; Shaojun Zhao; Jian Weng; Zhu Li; Liping Sun (Taylor & Francis Group, 2022)
Chemotherapy is commonly used for the treatment of lung cancer, but strong side effects and low treatment efficacy limit its clinical application. Here, extracellular vesicles (EVs) as natural drug delivery carriers were used to load conventional anticancer drug doxorubicin (DOX) and a chemosensitizer lonidamine (LND). Two types of EVs with different sizes (16k EVs and 120k EVs) were prepared using different centrifugation forces. We found that co-delivery of DOX and LND with both EVs enhanced the cytotoxicity and reduced the dose of the anticancer drug significantly in vitro. Effective delivery of anti-cancer drugs to cancer cells was achieved by direct fusion of EVs with the plasma membrane of cancer cells. On the other hand, DOX and LND inhibited cancer cell proliferation by increasing DNA damage, suppressing ATP production, and accelerating ROS generation synergistically. DOX and LND loaded EVs were also applied to the mouse lung cancer model and exhibited significant anticancer activity. In vivo study showed that smaller EVs exhibited higher anticancer efficiency. In conclusion, the co-delivery of the anticancer drug and the chemosensitizer with EVs may have potential clinical applications for cancer therapy.